The impact of implementation of rapid blood culture identification panels on antimicrobial optimization: a retrospective cohort study - Tyler Martin; Eli Wilber; Shreena Advani; Joseph Torrisi; Manish Patel; Paulina A. Rebolledo; Yun F. Wang; Sheetal Kandiah (Antimicrobial Stewardship & Healthcare Epidemiology, 2024)
Abstract